Trauma-focused exposure therapy for chronic posttraumatic stress disorder in alcohol and drug dependent patients: A randomized controlled trial - Coffey, Scott F; Schumacher, Julie A; Nosen, Elizabeth; Littlefield, Andrew K; Henslee, Amber M; Lappen, Amy; Stasiewicz, Paul R (Psychology of addictive behaviors, 2016)
To test whether a modified version of prolonged exposure (mPE) can effectively treat posttraumatic stress disorder (PTSD) in individuals with co-occurring PTSD and substance dependence, an efficacy trial was conducted in which substance dependent treatment-seekers with PTSD (N = 126, male = 54.0%, White = 79.4%) were randomly assigned to mPE, mPE + trauma-focused motivational enhancement session (mPE + MET-PTSD), or a health information-based control condition (HLS). All participants were multiply traumatized; the median number of reported traumas that satisfied DSM-IV Criterion A for PTSD was 8. Treatment consisted of 9-12 60-min individual therapy sessions plus substance abuse treatment-as-usual. Participants were assessed at baseline, end-of-treatment, and at 3- and 6-months posttreatment. Both the mPE and mPE + MET-PTSD conditions achieved significantly better PTSD outcome than the control condition. The mPE + MET-PTSD and mPE conditions did not differ from one another on PTSD symptoms at end of treatment, 3-, or 6-month follow-up. Substance use outcomes did not differ between groups with all groups achieving 85.7%-97.9% days abstinent at follow-up. In regard to clinically significant improvement in trauma symptoms, 75.8% of the mPE participants, 60.0% of the mPE + MET-PTSD participants, and 44.4% of the HLS participants experienced clinically significant improvement at the end-of-treatment. Results indicate mPE, with or without an MET-PTSD session, can effectively treat PTSD in patients with co-occurring PTSD and substance dependence. In addition, mPE session lengths may better suit standard clinical practice and are associated with medium effect sizes. (PsycINFO Database Record